2017
DOI: 10.18632/oncotarget.19625
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin 1 expression predicts prognosis and benefits from adjuvant chemotherapy in patients with gallbladder carcinoma

Abstract: BackgroundAbnormal expression of Stathmin 1(STMN1) plays an important role in the proliferation and migration of gallbladder carcinoma (GBC). The purpose of current study is to investigate the prognostic significance of STMN1 in GBC patients after surgery.MethodsSTMN1 expression was evaluated with immunohistochemistry (IHC) on tissue microarrays from 70 GBC patients from a single institution between 2009 and 2013. The correlation between STMN1 expression and clinicopathological profiles and the prognosis was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Taken together, our meta-analysis demonstrated that TMN1 could be used as a prognostic biomarker and a potential therapeutic target in solid tumors. 13,14,24-27,30,32-35,40,42, 12,13,16,[26][27][28]31,32,36,39,41,43,44 13 1.99 (1.51-2.61) < 0.05 86.1 < 0.05 Random effect NOS ⩾ 7 14,24,25,29,30,[33][34][35]37,38,40,42 Nevertheless, several limitations should be considered with much caution in this meta-analysis, when interpreting our synthesized result. First, the most important limitation was that there was significant heterogeneity, and our sensitivity and subgroup analysis failed to identify its sources.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Taken together, our meta-analysis demonstrated that TMN1 could be used as a prognostic biomarker and a potential therapeutic target in solid tumors. 13,14,24-27,30,32-35,40,42, 12,13,16,[26][27][28]31,32,36,39,41,43,44 13 1.99 (1.51-2.61) < 0.05 86.1 < 0.05 Random effect NOS ⩾ 7 14,24,25,29,30,[33][34][35]37,38,40,42 Nevertheless, several limitations should be considered with much caution in this meta-analysis, when interpreting our synthesized result. First, the most important limitation was that there was significant heterogeneity, and our sensitivity and subgroup analysis failed to identify its sources.…”
Section: Discussionmentioning
confidence: 94%
“…We then reviewed the full text of the remaining records at length; ultimately, 25 studies were determined eligible for this meta-analysis. 1214,16,2444…”
Section: R‑esultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus showed that STMN1 levels were adversely associated with the clinical prognosis of AML patients. STMN1 has been found to be a potential prognostic marker for patients with different types of tumors, including colon cancer (Zhang et al, 2016), gastric cancer (Bai et al, 2017), pancreatic ductal adenocarcinoma (Li et al, 2015), meningioma (Wang et al, 2017a), gallbladder carcinoma (Bo et al, 2017), osteosarcoma (Zhao et al, 2018), esophageal squamous cell carcinoma (Ni et al, 2017), (Hsieh et al, 2010) and non-small cell lung cancer (Nie et al, 2015;Wang et al, 2017b). Our data and previous reports indicated that STMN1 may not be only a prognostic marker for solid cancer but could also serve as a prognostic marker for patients with leukemia.…”
Section: Discussionmentioning
confidence: 99%